New species of the spider genera Aysenia and Aysenoides from Chile and Argentina: description and phylogenetic relationships (Araneae: Anyphaenidae, Amaurobioidinae) - Laborda, Alvaro (2013)
New spider species of the genera Aysenia Tullgren and Aysenoides Ramírez are described and their phylogenetic relationships discussed. The new species Aysenia paposo, from the coastal desert in northern Chile is sister to Aysenia araucana Ramírez. The diagnosis of Aysenia araucana is updated and new somatic variability is reported for the species. We present new records for other species of Aysenia and Aysenoides. The new species Aysenoides simoi, from temperate forests in Chile and adjacent Argentina is sister to Aysenoides nahuel. The phylogenetic analysis confirmed the monophyly of both genera. The support values of the genera are relatively high, but some internal branches show low support values. The genus Aysenia is supported by three synapomorphies, two of these from leg spination and one from the male genitalia. Aysenoides is supported by three synapomorphies from male and female genitalia.